2020
DOI: 10.1136/bmjopen-2019-032838
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the KidneyWise toolkit on chronic kidney disease referral practices in Ontario primary care: a prospective evaluation

Abstract: ObjectivesChronic kidney disease (CKD) is common; therefore, coordination of care between primary care and nephrology is important. Ontario Renal Network’s KidneyWise toolkit was developed to provide guidance on the detection and management of people with CKD in primary care (www.kidneywise.ca). The aim of this study was to evaluate the impact of the April 2015 KidneyWise toolkit release on the characteristics of primary care referrals to nephrology.Design and settingThe study was a prospective pre-post design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…On the other hand, with higher albuminuria, regression becomes improbable and expedited referral for specialist care may be warranted. Although there is consensus that nephrology referral should occur once eGFR is less than 30 mL/min/1.73 m 2 (stage G4 CKD), guidelines differ regarding referral recommendations based on ACR . We found that compared with people with G3b CKD with ACR less than 3 mg/mmol (54% of the cohort), those with G3b CKD and ACR of 30 to 59 mg/mmol CKD (2% of the cohort) had 44% to 60% lower hazard rates of regression.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…On the other hand, with higher albuminuria, regression becomes improbable and expedited referral for specialist care may be warranted. Although there is consensus that nephrology referral should occur once eGFR is less than 30 mL/min/1.73 m 2 (stage G4 CKD), guidelines differ regarding referral recommendations based on ACR . We found that compared with people with G3b CKD with ACR less than 3 mg/mmol (54% of the cohort), those with G3b CKD and ACR of 30 to 59 mg/mmol CKD (2% of the cohort) had 44% to 60% lower hazard rates of regression.…”
Section: Discussionmentioning
confidence: 80%
“…G4 CKD), guidelines differ regarding referral recommendations based on ACR. 8,11,12 We found that compared with people with G3b CKD with ACR less than 3 mg/mmol (54% of the cohort), those with G3b CKD and ACR of 30 to 59 mg/mmol CKD (2% of the cohort) had 44% to 60% lower hazard rates of regression. This small subset of patients with eGFR greater than 30 mL/min/1.73 m 2 (stage G3b CKD) and ACR 30 to 59 mg/mmol may benefit from earlier nephrology referral, as recommended by some (but not all) guidelines.…”
Section: Jama Network Open | Nephrologymentioning
confidence: 89%
See 3 more Smart Citations